DISTINCT ETIOLOGICAL INFLUENCES ON OBSESSIVE–COMPULSIVE SYMPTOM DIMENSIONS: A MULTIVARIATE TWIN STUDY. Issue 3 (2nd December 2015) - López‐Solà, Clara; Fontenelle, Leonardo F.; Verhulst, Brad; Neale, Michael C.; Menchón, José M.; Alonso, Pino; Harrison, Ben J.
Abstract : Background: Obsessive–compulsive disorder (OCD) is characterized by five major dimensions, including contamination/washing, harm/checking, symmetry/ordering, hoarding, and forbidden thoughts. How these dimensions may relate etiologically to the symptoms of other obsessive–compulsive related disorders (OCRDs) and anxiety disorders (ADs) is not well known. The aim of this study was to examine the genetic and environmental overlap between each major obsessive–compulsive dimension with the symptoms of other OCRDs and ADs. Methods: Two thousand four hundred ninety‐five twins of both sexes, aged between 18 and 45 years, were recruited from the Australian Twin Registry. Measures used scores on four dimensions (obsessing (forbidden thoughts), washing, checking, and ordering) of the Obsessive–Compulsive Inventory–Revised, Dysmorphic Concerns Questionnaire, Hoarding Rating Scale, Anxiety Sensitivity Index, Social Phobia Inventory, and Stress subscale of the Depression, Anxiety, and Stress Scale. Multivariate twin modeling methods using continuous and categorized variables were performed, also controlling for age and gender. Results: Our findings suggested that forbidden thoughts and washing demonstrated the strongest genetic overlap with other AD symptoms, while ordering was genetically related to OCRD symptoms. Common genetic influences on checking symptoms were best estimated when modeling OCRDs together with AD symptoms. Common environmental factors of ordering and checking were shared with AD symptoms. Conclusions: Important shared genetic and environmental risk factors exist between OCD, OCRDs, and ADs, but which vary alongside the expression of its major dimensions.